THE EFFECT OF ZEOLITE ADMINISTRATION IN THE CONSORTIUM OF HEAVY METAL REDUCING BACTERIA Pb ON LIQUID WASTE OF TEXTILE INDUSTRY - Ni'matul Murtafi'ah; Suci Rizki Nurul Aeni; Erika Setyowati (JBIO: jurnal biosains (the journal of biosciences), 2023)
Textile industry wastewater treatment must be managed properly so as not to cause environmental pollution that has an impact on human health. Industrial wastewater treatment by utilizing microbial activity with the addition of zeolite with varying concentrations measured using UV-Vis Spectrophotometry. This study aims to find out the effect of variations in zeolite concentration on bacterial consortiums in reducing lead heavy metals (Pb) and find out the characteristics of bacteria reducing heavy metals Pb after added zeolite. The results of the study using UV-Vis Spectrophotometry showed that the concentration of zeolite 3% was able to reduce heavy metals Pb on the 14th day with consecutive levels of 0.473 with an initial lead content of 2,460 ppm. The most significant decrease occurred in the addition of a zeolite concentration of 3%. This is shown in its effectiveness value of 86.772%. From this study, it can be concluded that the administration of a concentration of 3% in a consortium of bacteria can lower the levels of heavy metals Pb. Based on the characteristics of bacteria in biochemical tests, namely the confectionery test (Maltose, Glucose, Sucrose) obtained positive results, negative Lactose test, red /red TSIA test, negative marker test, and positive. Basil-shaped gram-negative bacteria refer to the genus Desulfobacter.